Analysis of Market Development Challenges and Opportunities Bonds in Papua Land - Sayful Saputra; Fathirul Akmal; Meilani Sukma Ayu; Tahiruddin Tahiruddin (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2024)
In the context of developing the bond market in Tanah Papua, there are several major challenges such as lack of market infrastructure, low financial literacy, and limited access to bond products. This study aims to analyze the opportunities arising from rapid economic growth, increasing infrastructure needs, and abundant natural resource potential in this region. The method used is a qualitative approach through literature review and conceptual analysis. The results of the study indicate that with the right strategies, such as building market infrastructure, increasing financial literacy, and developing innovative bond products, Tanah Papua has great potential to develop a strong and sustainable bond market. The conclusion of this study is that developing the bond market in Tanah Papua can be the key to accelerating economic development and community welfare by addressing challenges through a holistic strategic approach. This study provides useful input for relevant stakeholders in efforts to develop the bond market in Tanah Papua, so that it can support economic growth and the welfare of the local community as a whole.